A elevação do companheiro à condição de herdeiro necessário à luz do princípio da vedação ao retrocesso - Morais, Kennedy de (2021)
The present work intends to demonstrate, through a brief historical evolution and under the constitutional interpretation, based on the principle of the prohibition of retrogression, that the partner must be raised to the condition of necessary heir, under the terms of article 1.845 of the Civil Code. It will also demonstrate that this understanding is supported by the arguments used by the Supreme Court in the judgment of General Repercussion 809, which presents the unconstitutionality of article 1.790 also of the Civil Code